Low conservation value of converted habitat for avifauna in tropical peatland on Sumatra, Indonesia. Issue 2 (1st February 2016) - Fujita, Motoko S.; Samejima, Hiromitsu; Haryadi, Dendy Sukma; Muhammad, Ahmad; Irham, Mohammad; Shiodera, Satomi
Abstract: Peat swamp forest is an important refuge for biodiversity in Southeast Asia and is now becoming a target of exploitation. The scarcity of information on avifauna and ecology of birds in peat swamp forests prevents understanding of the effects of land use change on avifauna. In this study, we describe the bird assemblages in habitats with different land uses by comparing species richness, community composition, and feeding guild patterns in Bukit Batu, Indonesia. Bird assemblages in natural peat swamp forests (NPF), high‐maintenance industrial acacia plantations (planted acacia forest, PAF), low‐maintenance rubber plantations (jungle rubber forest, JRF), and village areas (VIL) were studied using a fixed‐radius point‐count method. Of the 95 species observed, 45, 20, 35, and 48 species were observed in NPF, PAF, JRF, and VIL, respectively. Estimated species richness was the highest in NPF, followed by VIL, JRF, and PAF. NPF had the highest species diversity and β‐diversity, more endangered species, and a distinctive species composition characterized by fly‐catching insectivores. The relative conservation value of PAF was notably low, particularly compared with JRF. The avifauna in VIL was characterized by more generalists that favor open spaces and therefore is not considered an important habitat for forest‐dependent birds that are of conservation concern. Our results indicate that NPF has irreplaceable value for bird diversity conservation, but low‐maintenance rubber plantations were home to several forest‐dependent species and partially supported bird diversity, particularly compared with high‐maintenance acacia plantations.